If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + 15 = 3x + -10 Reorder the terms: 15 + 25x = 3x + -10 Reorder the terms: 15 + 25x = -10 + 3x Solving 15 + 25x = -10 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 15 + 25x + -3x = -10 + 3x + -3x Combine like terms: 25x + -3x = 22x 15 + 22x = -10 + 3x + -3x Combine like terms: 3x + -3x = 0 15 + 22x = -10 + 0 15 + 22x = -10 Add '-15' to each side of the equation. 15 + -15 + 22x = -10 + -15 Combine like terms: 15 + -15 = 0 0 + 22x = -10 + -15 22x = -10 + -15 Combine like terms: -10 + -15 = -25 22x = -25 Divide each side by '22'. x = -1.136363636 Simplifying x = -1.136363636
| log(y)=-3log(x) | | 27=-4x+7x-6 | | 15=8+.75x | | 5-3(4-2m)=4(m-3)-3 | | 5m+3(m-2)=6m-12 | | -2-7a=8-5a | | 5(2n+3)=8(6n+1)+4 | | -184=6-8(7-8n) | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 7m-(9-4m)=3(m-11) | | Y+3.9=11.8 | | -184=-8(7-8n) | | Y+3.9=11.8 | | 7m-(9-4m)=3(m-11) | | x^2+4x+2.2=0 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | -3d+-28=-40 | | -184=-8(7-8n) | | 16x-14=3(4x-5)+4x+1 | | 7m-(9-4m)=3(m-11) | | 7-2n=n+4 | | 8x+23=-5 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 8x+23=-5 | | 16x-14=3(4x-5)+4x+1 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | -184=-8(7-8n) | | 7+2(3c+1)=6c+9 | | 7-2n=n+4 | | 7+2(3c+1)=6c+9 | | 7m-(9-4m)=3(m-11) | | 8x+23=-5 |